Immediately loaded blade implants. A histological and histomorphometrical evaluation after a long loading period. A retrospective 20 years analysis (1989-2009) - Iezzi, Giovanna; Scarano, Antonio; Perrotti, Vittoria; Tripodi, Domenico; Piattelli, Adriano (Journal of Osseointegration, 2012)
Aim Although the presence of mineralized tissues at the interface with blade implants has been reported, the view that blade implants cannot integrate still persists. Blades are the immediately loaded implants with the longest clinical history, so their histological evaluation may give results applicable to root-form implants. The aim of the present retrospective study was a histological evaluation of the peri-implant tissues in immediately loaded human blade implants retrieved after a long loading history. Materials and methods Thirty-one implants were included in the present report, after a loading history varying from 2 to 23 years, with a mean of 15 years. The implants were processed for histological examination. Results Histologically, the bone was in close and tight contact with the implants surface and no gaps or connective fibrous tissues were present at the implant-bone interface. The peri-implant bone was compact, mature, with the presence of small marrow spaces and Haversian canals. Many osteons were in contact with the implant surface. Most Haversian systems ran perpendicular to the major axis of the blades. In some fields it was possible to observe the presence of a few osteoblasts. Remodelling areas were present. Mean bone to implant contact percentage was, for all 31 implants, 43±5.2%. Conclusion The present report showed that immediately loaded blade implants can achieve and maintain osseointegration under long-term function (more than 20 years).